1998
DOI: 10.1021/ma981089k
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation in Poly(oxyethylene)−Poly(oxybutylene) Diblock Copolymers

Abstract: Twenty-six poly(oxyethylene)-poly(oxybutylene) diblock copolymers were prepared by anionic polymerization. The phase behavior of these copolymers was studied near the order−disorder transition over the composition range from 0.21 to 0.84 poly(oxyethylene) volume fraction. Small-angle X-ray scattering was used to characterize phase transition temperatures and ordered state symmetries. Four distinct microstructures were observed:  body-centered cubic, hexagonally packed cylinders (hex), lamellae (lam), and a bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 38 publications
6
63
0
2
Order By: Relevance
“…Rather, it suffices to choose values that map our χ model system qualitatively onto the experimental structure. A relationship between (or in this χ case, N) and temperature T that is commonly used is [40,41] These values produce reasonable interfacial structures, as shown in Figure 5 for T=2.0 and T=2.5 at the two different pressures. To assign specific units to the temperature such as Kelvin or degrees centigrade, the parameters A should be specified in the desired units.…”
Section: Surface Tension As a Function Of Temperature And Pressurementioning
confidence: 99%
“…Rather, it suffices to choose values that map our χ model system qualitatively onto the experimental structure. A relationship between (or in this χ case, N) and temperature T that is commonly used is [40,41] These values produce reasonable interfacial structures, as shown in Figure 5 for T=2.0 and T=2.5 at the two different pressures. To assign specific units to the temperature such as Kelvin or degrees centigrade, the parameters A should be specified in the desired units.…”
Section: Surface Tension As a Function Of Temperature And Pressurementioning
confidence: 99%
“…14 Numerous experimental and theoretical studies have shown that the morphology and domain spacing of nanophase-separated block copolymers can be predictably controlled by varying the degree of polymerization ( N ), the volume fraction ( f ), and the interaction parameter between blocks (χ). 510 Block copolymers containing polydimethylsiloxane (PDMS) are particularly desirable, as the generally high incompatibility between siloxanes and many organic components facilitates ordered phase separation at low N , yielding correspondingly small features. 11,12 For example, our group has utilized the high χ and etch contrast between blocks in PDMS- b -poly(lactic acid) to create ordered arrays of sub-20 nm features.…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers have been the subject of much research over the last three decades, largely due to the interesting behaviour of amphiphilic species [25][26][27][28][29][30][31]. In these polymeric systems the blocks show differing affinity towards a potential solvent and, frequently, a tendency to avoid mixing of dissimilar blocks with one another.…”
Section: Introductionmentioning
confidence: 99%